Conversion Surgery for Stage IV Gastric Cancer - Zhang, Fei; Huang, Xuanzhang; Song, Yongxi; Gao, Peng; Zhou, Cen; Guo, Zhexu; Shi, Jinxin; Wu, Zhonghua; Wang, Zhenning (Frontiers in Oncology, 2019)
The prognosis of stage IV gastric cancer (GC) is poor, with palliative chemotherapy remaining the main therapeutic option. Studies increasingly indicate that patients with unresectable stage IV GC, who undergo gastrectomy with radical intention after responding to several regimens of combined chemotherapy, can achieve good survival outcomes. Thus, surgery aiming at radical resection for unresectable stage IV GC after combined chemotherapy has received increasing attention in recent years. This novel therapeutic strategy was defined as conversion surgery in patients with unresectable stage IV GC and it can associate with significant improved survival when R0 resection can be achieved. Despite the recent advances in conversion surgery for patients with unresectable stage IV GC, selection criteria for combination chemotherapy regimens, indications for conversion surgery, optimal timing to surgery, and postoperative chemotherapy all remain controversial. This article reviews the current state of conversion surgery for unresectable stage IV GC.